A new species of Haliotrema (Monogenea: Ancyrocephalidae (sensu lato) Bychowsky & Nagibina, 1968) from holocentrids off Langkawi Island, Malaysia with notes on the phylogeny of related Haliotrema species. Issue 1 (February 2019) - Soo, O.Y.M.
Abstract: Haliotrema susanae sp. nov. is described from the gills of the pinecone soldierfish, Myripristis murdjan off Langkawi Island, Malaysia. This species is differentiated from other Haliotrema species especially those from holocentrids in having a male copulatory organ with bract-like extensions at the initial of the copulatory tube, grooved dorsal anchors and ventral anchors with longer shafts. The maximum likelihood (ML) analysis based on partial 28S rDNA sequences of H . susanae sp. nov. and 47 closely related monogeneans showed that H . susanae sp. nov. is recovered within a monophyletic clade consisting of only species from the genus Haliotrema . It is also observed that H . susanae sp. nov. forms a clade with H . cromileptis and H . epinepheli which coincides with a similar grouping by Young based on solely morphological characteristics. The morphological and molecular results validate the identity of H . susanae sp. nov. as belonging to the genus Haliotrema . Graphical abstract: Highlights: First record and description of a new Haliotrema species from Myripristis murdjan off Malaysian waters. Molecular relationship of new species tested against other closely-related monogenean species. Brief discussion about status of Haliotrema species and efforts to reclassify current species.